Calculation of hydrodynamic coefficients of ship sections in roll motion using Navier-Stokes equations. (15th March 2017) - Lavrov, A.; Rodrigues, J.M.; Gadelho, J.F.M.; Guedes Soares, C.
Abstract: The flow in the vicinity of 2D ship sections carrying out forced roll motions is simulated using the solution of the Navier-Stokes equations implemented in OpenFOAM. A hybrid Lagrangian-Eulerian adaptive mesh scheme is applied to solve forced motions on ship sections oscillating in calm water as well as the free surface capturing problem. Three sections of a containership, with differing geometrical properties, are investigated by comparing viscous unsteady results with potential flow solutions. The method presented in this study has been validated by comparing numerical results with experiments performed on a rectangular section. The influence of viscosity, particularly on vortex shedding, on the roll motion is investigated for an array of oscillation frequencies. Highlights: Forced roll of 2D ship sections is simulated using the Navier-Stokes solution in OpenFOAM. A hybrid Lagrangian-Eulerian adaptive mesh is applied to the body and free surface interface tracking. The hydrodynamic coefficients of three sections of a containership, are compared with potential flow results. The influence of viscosity, particularly on vortex creation, on the roll motion is investigated.